Analysis of the Zero Rupiah Passport Policy in Supporting Passport Issuance for Prospective Indonesian Migrant Workers - Dwiki Praditya; Intan Nurkumalawati; Pascalis Danny Kristi Wibowo (Univiversitas Dr. Djar Wattiheluw, 2025)
This study examines the Zero Rupiah Passport Policy as a form of state intervention designed to support the protection and fulfillment of Indonesian migrant worker candidates’ administrative rights, especially in the passport issuance process. Employing a qualitative-descriptive method through literature review of policy documents, regulations, and prior studies, the research identifies how the policy reduces financial barriers while signaling the government’s commitment to strengthening migration governance. Nevertheless, challenges persist, including limited dissemination, unequal institutional readiness, and disparities in regional implementation. The study contributes theoretically by mapping the policy framework through its stages of formulation, implementation, and impact, while recommending further evaluative and field- based research. In doing so, it enriches academic discourse on inclusive and equitable public service and migration policies.